Metode AHP Dan SAW Dalam Penentuan Penutupan Ruas Jalan Sebagai Upaya Pencegahan Penyebaran Covid-19 - Sandi probo sarjono; Istiadi Istiadi; Fitri Marisa (Fakultas Ilmu Komputer, 2021)
The President of the Republic of Indonesia issued Presidential Decree Number 7 of 2020 concerning the Task Force for the Acceleration of Handling of Corona Virus Desease 2019. This decision was followed up by all Regional Leaders as the basis for the formation of a Regional Level Task Force, one of which is Malang Regency, East Java Province. One of the efforts is to implement Physical Distancing at the sub-district level, namely by closing existing roads in Malang Regency with the aim of reducing the activity of people and vehicles on these roads. The problem is how to determine the most appropriate road sections to be closed so that the policy is right on target. The decision support system application and the calculation of data obtained using the Simple Additive Weighting (SAW) and Analytical Hierarchy Process (AHP) methods can help make decisions in determining which roads will be closed. The application of these two methods is able to analyze data and provide accurate calculation results so that it can provide appropriate alternative solutions. There are differences in the results of calculations and rankings in the two methods, each method provides a value that can be used as an alternative as a choice of roads to be closed as needed.